Foreign businessmen and the financing of trade to the Indies in the second half of the 18th century. - Brilli, Catia; Bartolomei, Arnaud; Kaps, Klemens (Anuario de Historia de América Latina, 2025)
This article examines the intermediary role of foreign merchants (especially French, Genoese, and Milanese businessmen) in managing European trade with the Indies through the Spanish port of Cadiz towards the end of the ancient regime, by focusing on the ways they structured their participation and the instruments they used to finance this trade. We argue that foreign merchants operated in two different institutional environments depending on the nature of their business: with their European partners, they relied upon the classical instruments of intra-European trade (such as account books, bills of exchange and commission contracts); with the cargadores, the merchants who were legally enable to participate in the Spanish transoceanic trade, they pooled European merchant and financial capital into the American markets by massively (albeit not exclusively) resorting to sea loans. The article not only discusses the persistent use of this instrument and its profitability, but also and the possible reasons for its decline in the last decades of the century.